THE EFFECT OF PUBLIC INFORMATION ON TAX COMPLIANCE MEDIATED BY TAXPAYERS' UNDERSTANDING OF MSMES IN PEKANBARU - Rahmi, Febri; Elfiandri, Elfiandri; Elfera, Shahedah Soeci (Economic and Science Faculty of Islamic State University, 2023)
The government as a public service provider has provided public information disclosure and ease of access. The beneficiaries of information such as tax information are MSMEs. MSMEs as contributors to the country's foreign exchange have received tax stimulus, such as lowering rates, but have not been good enough to increase taxpayer compliance. Therefore, it is necessary to conduct a study aimed at analyzing the effect of public information on tax compliance mediated by the understanding of taxpayers. The research sample was 316 people, with incidental purposive sampling technique. Data was collected by distributing questionnaires. Data analysis method using Structural Equation Model. Previous research has not discussed public information with tax compliance. The results of the study stated that partially public information and understanding of taxpayers had a significant positive effect on tax compliance. The understanding of taxpayers can mediate the relationship between public information and taxpayer compliance. The amount of public information contribution can explain tax compliance mediated by taxpayer understanding is 47%, the rest is influenced by other variables. These variables are tax transparentcy, information regarding the past degree of tax evasion, fiscal transparency and individual behavior that can be studied in next studies